The effects of the phenomenon of extremism on intellectual security - Al-Harbi, Majed Marzoug (Journal of Islamic Sciences, 2025)
The current research aimed to understand the effects of extremism on intellectual security from both doctrinal and social perspectives. This was done to demonstrate the effects of extremism and its pervasiveness in contemporary intellectual security issues in the Islamic world. It then sought to shed light on these issues and identify their causes، thereby creating a high-quality mental picture that will help us avoid their causes and enhance intellectual security in the Islamic world. The research reached the following conclusions: -Extremism incites division، spreads excommunication، and divides ranks. It also plays havoc with the minds of young people، leading them to dark projects and nihilistic massacres that disrupt intellectual security، where truth is not upheld and falsehood is not challenged. -Extremism is a departure from intellectual security and normal human nature and a violation of the innate nature with which God created people. Extremism is intolerable to human nature، and those who are accountable cannot tolerate it.